KESESUAIAN ANTARA CITA-CITA DAN PEMILIHAN PROGRAM STUDI MAHASISWA FAKULTAS AGAMA ISLAM ANGKATAN 2013/1014 - Shobahiya, Mahasri; Lestari, Risma Marno (Tajdida, 2014)
The success of ones learning is influenced by the ideals to be achieved. This study answered about compatibility  of dream and selection courses year 2013/2014. By using a quantitative approach  this field research leads to the conclusion that, variety of dream year 2013/2014 is to be a teacher IS (36%), lecturers IS (7%), psychologists (2%), enterpreuner (9%) , bank employees (6%), the judge / prosecutor (1%), director (2%), undergraduate (1%), and others (36%). Students of Islamic studies-Tarbiyah  that match with mission and objectives of major is quite large (62%), which aspires to be a teacher and lecturer of IS. Students of Islamic law (Sharia) in accordance with the ideals and objectives of faculty mission are very small (3%), which aspires to be a judge year 2013/2014, to be a teacher of IS (36%), lecturers of IS (7%), psychologists (2%), enterpreuner (9 %), bank clerks (6%), the judge / prosecutor (1%), director (2%), undergraduate (1%), and others (36%). Students Prodi PAI-Tarbiyah The dreams that match with its mission and objectives of faculty are quite large ( 62 % ) , who aspires to be a teacher and lecturer of IS. Students of Islamic law ( Sharia) that match with the ideals and objectives of the faculty is very small ( 3 % ) , which aspires to be a judge / prosecutor .